Intake Ratio of 131I to 137CS Derived from Thyroid and Whole-body Doses to Residents of Iwaki City in Japan's Fukushima Prefecture - Kim, Eunjoo; Yajima, Kazuaki; Igarashi, Yu; Tani, Kotaro; Hashimoto, Shozo; Nakano, Takashi; Akashi, Makoto; Kurihara, Osamu (Health physics (1958), 2021)
It is very important to determine the precise internal thyroid doses of Fukushima residents involved in the 2011 Fukushima nuclear disaster, particularly for small children. This has been challenging due to the lack of direct human measurements to identify 131I, the biggest contributor to the thyroid doses. We previously used a dataset of late whole-body counter (WBC) measurements targeting 134Cs and 137Cs for the thyroid dose estimation in comparison with the intake ratios of 131I to 137Cs (or 134Cs) derived from thyroid and whole-body doses individually obtained from different subject groups, assuming simultaneous acute intake via inhalation. Herein, we applied the same method to the doses of residents in Iwaki city (located south of the Fukushima Daiichi Nuclear Power Plant) with a relatively high activity ratio (131I/137Cs) for the ground deposition density. Our analyses revealed that the intake ratio (131I/137Cs) for the Iwaki residents was 4.2-4.3, which is relatively consistent with the values obtained in other studies (average 3.0-5.0). No regional difference in the intake ratios from other areas was observed, but further studies are required to determine the accurate intake ratio in the early phase of the accident, in particular focusing on the reasonable interpretation of results of the late WBC measurements to evaluate the actual Cs intake.